Analysis of Corn (Zea mays) Demand in Boyolali - Suswadi; Sari, Y.E. (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2023)
The research aims to analyze the factors of corn price, corn demand, and the elasticity of corn demand in Boyolali Regency. The basic method used in this research is analytical-descriptive. The selection of the research location was purposive, with Boyolali Regency chosen as the location due to the consistent increase in corn demand. The results of the data analysis using multiple linear regression reveal the equation Ln Qd = -367.983 - 0.191 Ln X1 + 0.541 Ln X2 + 0.875 Ln X3 - 0.729 Ln X4 + 27.253 Ln X5 + e. This model has an R?Â² value of 21.9%, indicating that 21.9% of the corn demand in Boyolali Regency cannot be explained by the variables of corn price, rice price, soybean price, per capita income, and population, while the remaining 78.1% is explained by other variables not studied. Based on the F-test, the combined effect of corn price, rice price, soybean price, per capita income, and population on corn demand in Boyolali Regency is not significant. The t-test for individual variables also indicates that corn price, rice price, soybean price, per capita income, and population have no significant effect on corn demand in Boyolali Regency at both 99% and 95% confidence levels. The coefficient of price elasticity is -0.191, indicating inelasticity as it is less than one. Rice price has a positive cross-elasticity value of 0.541, signifying that rice is a substitute good for corn. Soybean price has a positive cross-elasticity value of 0.875, also acting as a substitute for corn. The coefficient of income elasticity is -0.729, indicating that corn is an inferior good due to its negative sign.